Case Report: Microangiopathic Hemolytic Anemia With Normal ADAMTS13 Activity - Osti, Nicola; Beschin, Greta; Goldin, Marzia; Guidolin, Lucia; Panero, Enrico; Sartori, Alice; Parisi, Alice; Cantini, Maurizio; Pizzolo, Francesca; Olivieri, Oliviero; Friso, Simonetta (Frontiers in Medicine, 2021)
Thrombotic microangiopathies (TMAs) include a heterogeneous group of diseases characterized by abnormalities in the vessel walls of arterioles and capillaries resulting in microvascular thrombosis that typically presents with a microangiopathic hemolytic anemia (MAHA) and severe thrombocytopenia. We describe here the case of an 82-year-old woman, who came to our attention for a clinical condition consistent with thrombotic microangiopathy. Even if initially highly suggestive for a thrombotic thrombocytopenic purpura (TTP), the elevated ADAMTS13 activity together with the alteration of the main coagulation parameters (D-dimer elevation, fibrinogen consumption, slightly prolonged prothrombin time), induced us to consider several other diseases in the differential diagnostic process. The case evolved toward a suspected overlapped secondary hemophagocytic syndrome, though the hyperferritinemia was finally interpreted within the frame of a cytokine storm. After a complex diagnostic workup, the clinical and biochemical parameters guided us toward the diagnosis of a cancer-related microangiopathic hemolytic anemia (CR-MAHA) secondary to a relapsing breast cancer with multiple metastatic localizations. Prednisone 1 mg/kg body weight was started, and several units of fresh frozen plasma were infused, obtaining a good control of the hemolysis. No specific oncological therapies were, however, possible, due to the older age and the critically compromised general condition of the patient; therefore, after clinical stabilization, the patient was discharged for treatment in a palliative care Hospital.